2011
DOI: 10.1016/j.jaad.2010.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency facial rejuvenation: Evidence-based effect

Abstract: Although the results may not be as impressive as those obtained by ablative treatments, RF is a promising treatment option for photoaging with fewer side effects and downtime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
156
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(165 citation statements)
references
References 38 publications
7
156
2
Order By: Relevance
“…The use of the RF to treat facial and body skin laxity also has demonstrated clinical response positive, (13,14,15,16,17,18) however, in the literature there is a lack of studies that evaluate the therapeutic response of RF in laxity tissue of the labia majora. In this study, 100% of patients reported satisfaction with the appearance of their genitalia after treatment with RF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the RF to treat facial and body skin laxity also has demonstrated clinical response positive, (13,14,15,16,17,18) however, in the literature there is a lack of studies that evaluate the therapeutic response of RF in laxity tissue of the labia majora. In this study, 100% of patients reported satisfaction with the appearance of their genitalia after treatment with RF.…”
Section: Discussionmentioning
confidence: 99%
“…The swelling of the labia majora associated with decreased skinfold thickness, determined, in the view of the evaluators, a positive response from the appearance of the genitalia. This result is due to the retraction of existing collagen, and miro-remodeling (11,13,18) over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[8][9][10] In the medical field, RF energy has been used for over 80 years. 2,11 The initial application of RF to medicine was electrocautery in 1920s, but now RF is widely used for many medical conditions, ranging from surgery for minimal invasive technique to aesthetic procedures.…”
Section: History Of Radiofrequencymentioning
confidence: 99%
“…[8][9][10] RF devices generate electrical current using electromagnetic radiation. 2,10 When the current is applied to tissue, it encounters resistance, which is an inherent property of the particular tissue, also called as impedance.…”
Section: Radiofrequencymentioning
confidence: 99%